Mathematical model of training process for specialists on information technologies implementation into industry - Задонцев, Ю.В. (Proceedings of National Aviation University (archive), 2010)
The mathematical model of training for the introduction of information technology to production using different forms of learning. Analytical models allow to estimate the level of preparation of object of studies to the separate job processing after the cycle of preparation. Models take into account the entrance level of readiness of object, complex coefficient of accordance of terms of the conducted measures and level of mastering of knowledge, abilities and skills of object of studies.